The Importance of Literacy-Based Indonesian Language Learning for the 21st Century Students' Skills - Arina Amalia Prihartini; Siti Rohana Hariana Intiana; Fitriana Handayani; Khairul Faridi (Nusantara Science and Technology Proceedings, 2023)
Literacy and language are inseparable. When a person has acquired language skills, such as reading and writing, he is said to have good literacy skills. Literacy as the ability to read and write is the primary entry point for the expansion of literacy's broader meaning. Includes the ability to comprehend the explicit and implied meaning of sentences, paragraphs, and the overall text. This demonstrates that reading is a complex and time-consuming process. Therefore, literacy-based Indonesian language instruction is crucial for material mastery and solving students' everyday problems. Under the 2013 Curriculum's explanation that language is the driver of knowledge, Indonesian is a means of transmitting knowledge. In contrast, as we enter the 21st century, where the times are vastly different, the educational process requires the mastery of skills that are appropriate for the era. Schools must be able to teach students the future skills they will need. The 4 skills are the capacity for creative thought (creative thinking), critical thought and problem-solving (critical thinking and problem-solving), communication (communication), and collaboration (collaboration), also known as the 4Cs. Therefore, the implementation of literacy-based Indonesian language instruction is one of the processes for improving students' 21st-century skills.